Associations Between Physical Therapy Continuity of Care and Health Care Utilization and Costs in Patients With Low Back Pain: A Retrospective Cohort Study. Issue 12 (26th September 2018) - Magel, John; Kim, Jaewhan; Thackeray, Anne; Hawley, Charles; Petersen, Sterling; Fritz, Julie M
Abstract: Background: Patients who consult a physical therapist for low back pain (LBP) may receive initial and subsequent management from different therapists. The impact that physical therapy provider continuity has on health care use in patients with LBP is insufficiently studied. Objective: The objective of this study was to examine the impact of continuity of the physical therapy provider on health care use and costs in patients with LBP referred from primary care. Design: The study design included a retrospective analysis of claims data. Methods: Data from an all-payer claims database were examined. Logistic regression was used to evaluate the association between physical therapy provider continuity and health care use during the 1-year period following a visit with a primary care provider for LBP. Results: Patients who experienced greater physical therapy provider continuity had a decreased likelihood of receiving lumbar surgery. They also paid less (mean = ${\$}$ 1737 [95% confidence interval, ${\$}$ 1602–${\$}$ 1871]) than those who experienced less physical therapy provider continuity (mean = ${\$}$ 2577 [95% confidence interval, ${\$}$ 2008–${\$}$ 3145]). Limitations: The degree of causality between any predictor and outcome variables cannot be determined due to the observational nature of the study. Conclusions: Greater continuity of the physical therapy provider appears to be associated with a decreased likelihood of surgical treatment for LBP and lower health care costs related to LBP.